Implementation of Islamic Educational Philosophy in Educational Policy (2021–2024): Analysis of National Education Standards, the Merdeka Curriculum, and Madrasah Guidelines - suhaeni; Syayidah Afrohah; Rahmat Hidayatullah; Ahsan Hakim (Education Research Center, 2026)
This study examines how Islamic educational philosophy is operationalized within Indonesian education policy during 2021–2024. Anchored in three core philosophical orientations—faith and piety (iman–taqwa), moral formation (adab/akhlak), and holistic human development—the study maps these values onto binding policy instruments governing standards, curriculum, assessment, and institutional design. Using a normative–descriptive library research method, the analysis draws on six primary documents: Government Regulation (PP) No. 57/2021 and its amendment (PP No. 4/2022) on National Education Standards; Ministerial Regulations (Permendikbudristek) No. 5, 7, and 21 of 2022 on graduate competency, content, and assessment standards; Ministerial Decree No. 262/M/2022 on the learning-recovery curriculum guideline; Permendikbudristek No. 12/2024 on the Merdeka Curriculum; and the Minister of Religious Affairs' Decree (KMA) No. 347/2022 on Merdeka Curriculum implementation in madrasahs. The findings show that the 2021–2024 policy framework explicitly embeds faith, piety, and moral character in graduate outcomes, mandates religious education as compulsory content, and provides operational levers through standards-based design, intra–co–extracurricular activities, formative assessment, and madrasah-specific curriculum architecture. The article concludes by identifying policy implications and persistent implementation challenges at the school and madrasah level, including value reduction to cognitive knowledge, weak character assessment, uneven institutional capacity, and the need for cross-ministry synchronization.